PENGARUH MEDIA PEMBELAJARAN PUZZLE TERHADAP HASIL BELAJAR SISWA PADA TEMA 1 SUB TEMA 3 PERTUMBUHAN DAN PERKEMBANGAN MAKHLUK HIDUP KELAS III SD SWASTA HKBP TOMUAN PEMATANGSIANTAR - Grace Carolyn Rajagukguk; Melvin Simanjuntak; Aprido Bernando Simamora (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to determine the effect of Puzzle learning media on student learning outcomes in theme 1 subtheme 3 growth and development of living creatures in class III of HKBP Tomuan Pematangsiantar Private Elementary School.The type of research used in this research is experimental research. Research based on one group pretest-posttest design is research using experimental methods. The sample for this research was 21 class III students. The sampling technique in this research is Nonprobability Sampling. Data collection in this research used pretest and posttest. The pretest was carried out to determine students' initial abilities before carrying out the treatment and the posttest was carried out to determine student learning outcomes after treatment using Puzzle learning media. The test is in the form of objective test questions (multiple choice) having four choices, namely a, b, c, and d with a total of 20 questions.Based on the results of the N-Gain test, the maximum (ideal) score is the result of the initial and final trials with an N-Gain of 0.7>g>1 with the interpenetration